The Concept Of Tourism Destination Development In Indonesia Based On Socio-Economic In GSTC Criteria Using Bibliometric Approach - furqan, Furqan; Yogi Putra; Mega Hernawati Harefa; Tina Linda (International Journal of Economics and Management, 2025)
This study aims to answer the question of how much tourism destination managers in Indonesia have implemented a sustainability context by adopting the criteria that have been standardized in the global sustainable tourism council destination (GSTC-D) policy. This study uses a bibliometric method approach. The findings of the study are that out of 21 international studies indexed by Scopus, only 6 (six) studies focus on the development and management of sustainable tourism destinations in Indonesia using the GSTC-D approach. So this is a big challenge that needs to be faced together by both tourism destination managers and the Government and communities around tourist destinations to support each other in realizing sustainable tourism destinations throughout Indonesia. The conclusion is that subsequent research can study the management of sustainable tourism destinations in the cultural sector such as protection of cultural heritage, visiting cultural sites because Indonesia is rich in local wisdom, as well as studies on environmental impacts such as nature tourism conservation, resource management, and waste and emission management